The influence of antibiotics and dietary components on gut microbiota - Dudek-Wicher, Ruth K.; Junka, Adam; Bartoszewicz, Marzenna (Gastroenterology Review/Przegląd Gastroenterologiczny, 2018)
The gut microbiota acts as a real organ. It exerts important metabolic functions, and regulates the inflammatory response by stimulating the immune system. Gut microbial imbalance (dysbiosis) has been linked to important human diseases and inflammation-related disorders. The symbiotic interactions between resident microorganisms and the gastrointestinal tract significantly contribute to maintaining gut homeostasis. The present review summarizes our knowledge regarding the impact of different antibiotics causing such long-term consequences as decreased microbial diversity, modulation of the Bacteroidetes/Firmicutes ratio, Clostridium difficile overgrowth, and increased expansion of the opportunistic pathogens Salmonella typhimurium, Escherichia spp., and Klebsiella spp. Also, food additives, such as emulsifiers and artificial sweeteners, which are meant to reduce the risk of obesity and diabetes, may actually increase the risk of diseases due to microbial alterations. On the other hand, dietary components such as polyphenols, omega-3 acids or curcumin may positively affect gut microbiota composition.